Основы бизнеса: учебное пособие / Э. А. Арустамов - Арустамов Эдуард Александрович (Дашков и К°, 2006)
Экземпляры: ф14 (20231205) / Инвентарный номер: 42069 / Цена: 83.53 / Сис.шифр: 65.9(2Рос)09я7 / Авт.знак: А 86 / ГРНТИ: 06.56.21 / ББК: 65.9(2Рос)09я7